How To Deal With Unjust Laws: Justifiability Of Civil Disobedience - Alakbarova, Fatma (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
The issue of active protests against the injustice of the law aimed at bringing about a change in that conduct is of great relevance for members of the world society. There is no escape from admitting the fact that even the most perfect political system may and will from time to time produce unjust laws. What is as yet unclear is the principles of justification in favour of a civil disobedient who commits an open breach of that laws. The present article defines the features that make an act of civil disobedience something more than a simple breach of a law. The purpose of this article is to justify civil disobedience as a unique political category, which makes social choice and legal change possible.
Keywords: nieposłuszeństwo obywatelskie; sprawiedliwość; prawo; społeczeństwo; uzasadnienie